The Essential Role of Wearable Devices in the Future of Preventive Care - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The Essential Role of Wearable Devices in the Future of Preventive Care The landscape of healthcare is undergoing a profound transformation, shifting fr...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care